Exploring the Application of RFID for Designing Augmented Virtual Reality Experience - Ruowei Xiao; Aleksi Vianto; Asif Shaikh; Oguz'oz' Buruk; Juho Hamari; Johanna Virkki (IEEE Access, 2022)
Recent technical advancement has driven the boundary between the physical reality and digital virtuality to diminish significantly. As part of the emerging trend, existing research leverages a synergized use of Radio Frequency IDentification (RFID) and virtual reality (VR) to create compelling hybrid user experience. However, current state-of-the-art literature indicates a lack of coherent architecture for seamlessly integrating these two siloed technology stacks, thus hindering full-fledged mixed and extended reality applications. In this article, we first conducted a comprehensive literature review and identified key design themes and different technical affordances of RFID within VR context; in reflection of our findings, we hence proposed an overarching architecture to facilitate swift and flexible composition of RFID and VR; Three use cases were further established using the proposed architecture to both demonstrate its technical feasibility and qualitatively assess RFID’s augmentation over conventional VR applications. This exploratory research intends to offer some preliminary design knowledge and insights for designing and developing RFID-augmented VR applications, open up opportunities for further discussion and research interest in this area, thus ultimately contributing to more immersive, interactive and informative user experience.